Decoration of TiO2/g-C3N4 Z-scheme by carbon dots as a novel photocatalyst with improved visible-light photocatalytic performance for the degradation of enrofloxacin. Issue 54 (6th July 2017) - Su, Yuehan; Chen, Ping; Wang, Fengliang; Zhang, Qianxin; Chen, Tiansheng; Wang, Yingfei; Yao, Kun; Lv, Wenying; Liu, Guoguang
Abstract : A novel visible-light-driven CDs/TiO2 /g-C3 N4 photocatalyst was successfully synthesized by doping CDs in TiO2 nanoparticles and the surface of g-C3 N4 nanosheets via a facile hydrothermal process and was confirmed by characterization methods. Abstract : A novel visible-light-driven carbon dot (CDs)/TiO2 /g-C3 N4 photocatalyst was successfully synthesized by doping CDs in TiO2 nanoparticles and the surface of g-C3 N4 nanosheets via a facile hydrothermal process and was confirmed by characterization methods. UV-vis diffuse reflectance spectra (DRS) revealed that CDs/TiO2 /g-C3 N4 showed obvious additional absorption in the 370–450 nm region. DMPO spin-trapping ESR spectra demonstrated the existence of O2 ˙ − and ·OH. The photocatalytic activity of the CDs (1.0 wt%)/TiO2 /g-C3 N4 was remarkably enhanced as compared to that of the single components (TiO2 and g-C3 N4 ) and double component (TiO2 /g-C3 N4 ) towards the degradation of enrofloxacin (ENX) under visible-light irradiation. About 91.6% of ENX was decomposed by CDs (1.0 wt%)/TiO2 /g-C3 N4 in 1 h, which is nearly 3.95 times, 4.82 times, and 1.69 times that for TiO2, g-C3 N4, and TiO2 (90.0 wt%)/g-C3 N4, respectively. Scavenging experiments revealed that O2 ˙ − and ·OH played key roles during the photocatalytic degradation of ENX. This study provides a simple and convenient method to modify materials with enhanced photocatalytic performance, and the CDs/TiO2 /g-C3 N4 catalyst is efficient, stable, and reusable for environmental practical applications.